Dengzhanxixin injection for cerebral infarction: A systematic review and meta-analysis of randomized controlled trials. Issue 32 (August 2017) - Wang, Jia; Xie, Yanming; Zhao, Shitong; Zhang, Jiangsong; Chai, Yan; Li, Yuanyuan; Liao, Xing
Abstract: Background: No systematic review has been published in English of Dengzhanxixin (DZXX) injection for cerebral infarction. The aim of this systematic review was to assess the effects and safety of DZXX injection for cerebral infarction. Methods: Eight databases were searched from their inception. Randomized controlled trials (RCTs) related to DZXX for cerebral infarction in English or Chinese without restrictions on the publication status were included. Neurological deficit, quality of life, and response rates were analyzed. Adverse events were also investigated. Results: Twenty-three randomized controlled trials (RCTs) with 2291 participants were included. Meta-analysis showed that DZXX injection plus routine western therapy was better than routine western therapy alone for reducing neurologic deficit (MD –2.86, 95% CI –3.87 to –1.86), for improving quality of life (MD 9.48, 95% CI 8.34–10.63), and for improving response rates (RR 1.20, 95% CI 1.15–1.25). No serious adverse drug events (ADE) were reported. Conclusions: DZXX injection may have a potential therapeutic effect for cerebral infarction in reducing neurologic deficit, improving life quality and response rates. However, we could not draw any definitive conclusions due to the insufficient evidences. More high-quality trials are needed to provide more strong evidence and to assess the safety of DZXX injection.